Relationship between platelet density and platelet aggregation, ATP release, and cytosolic-free calcium mobilization in rabbits - LI Bai-yan; LI Wen-han; BAI Ying (Acta Pharmacologica Sinica; Vol 16, No 4 (July 1995): Acta Pharmacologica Sinica, 2016)
AIM: To study the relationship of platelet density and platelet functions, including aggregation, ATP release, and intracellular calcium mobilization. METHODS: Platelet density was evaluated by discontinuous gradients of Percoll and cytosolic-free calcium concentration in single platelets was measured by fluorescence and imaging. RESULTS: Rabbit platelets were assorted into 3 subpopulations using discontinuous gradients of Percoll: high density (HD, > 1.062, 20%-30%), intermediate density (ID, around 1.057, 40%-50%) and, low density (LD, < 1.051, 10%-15%). The sizes of platelets in these subpopulations were widely different (HD: 725 +/- 76; ID: 443 +/- 47; and LD: 307 +/- 46) and well correlated with the density (r = 0.988, P < 0.01). Thrombin 0.5 U-induced aggregations in the 3 subpopulations were 78 +/- 8%, 69 +/- 4%, and 62 +/- 3%, respectively and a difference was found between HD and LD (P < 0.05). The amounts of ATP released during aggregation were 4.7 +/- 0.9, 3.4 +/- 1.0, and 2.6 +/- 0.6 mumol/4 x 10(5) platelets in HD, ID, and LD groups, respectively. Thrombin 150 U-induced [Ca2+]i mobilization in HD (990 +/- 130 nmol L-1) was different (P < 0.01) from those in ID (410 +/- 80 nmol L-1) and LD (400 +/- 40 nmol L-1). Serotonin (5-HT) 3 mumol L-1 also caused [Ca2+]i mobilization in single-washed platelet subpopulations and results were similar to those of thrombin although it did not induce any detectable aggregation or release reaction. CONCLUSION: Platelet functions and intracellular calcium concentraotion were increased with platelet density in rabbits.